Steel fiber reinforced concrete ground slabs : a comparative evaluation of plain and steel fiber reinforced concrete ground slabs - Kearsley, Elsabe P. (University of Pretoria, 2013)
Dissertation (Dissertation (MEng)--University of Pretoria, 2001)--University of Pretoria, 2001.